2020
DOI: 10.3389/fmed.2020.566278
|View full text |Cite
|
Sign up to set email alerts
|

“What About Automated Pain Recognition for Routine Clinical Use?” A Survey of Physicians and Nursing Staff on Expectations, Requirements, and Acceptance

Abstract: Background: Over the last 12 years, the fundamentals of automated pain recognition using artificial intelligence (AI) algorithms have been investigated and optimized. The main target groups are patients with limited communicative abilities. To date, the extent to which anesthetists and nurses in intensive care units would benefit from an automated pain recognition system has not been investigated.Methods:N = 102 clinical employees were interviewed. To this end, they were shown a video in which the visionary te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 24 publications
(18 reference statements)
0
9
0
Order By: Relevance
“…Findings from research based on the BioVid ( 30 ) & X-ITE ( 24 ) datasets, the results of the present study, staff acceptance ( 29 ), and patient acceptance indicate that it would now be appropriate to develop and test an APR prototype.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Findings from research based on the BioVid ( 30 ) & X-ITE ( 24 ) datasets, the results of the present study, staff acceptance ( 29 ), and patient acceptance indicate that it would now be appropriate to develop and test an APR prototype.…”
Section: Discussionmentioning
confidence: 69%
“…This would be a key benefit for clinical staff. Walter et al (29) showed that the majority of clinical staff in the ICU would prefer a biosignal-based pain detection. In relation to this, facial EMG would have the benefit of replacing computer vision, in terms of cost effectiveness and data security.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies did not observe an effect 50 , 52 . Walter et al 53 found that 55.8% of younger participants claimed that they would use automated pain recognition. In the older age group, only 40.4% of respondents reported that they would use the system ( N = 102) 53 .…”
Section: Resultsmentioning
confidence: 99%
“…Automated pain recognition (APR) is an external observation method into which hardware and software components with artificial intelligence (AI) are integrated (Walter et al, 2020). Automated pain recognition systems may be based on pain behaviours, as facial expressions, vocalization and avoidance movements, and/or physiological signals (heart rate, pupillary diameter, …).…”
Section: Introductionmentioning
confidence: 99%